Quick reference guide for paediatric emergencies seizing the golden hours - De Munter, Claudine. (Imperial College Press ; Distributed by World Scientific Pub. Co., 2014)
This is the essential aide memoir for clinicians who are dealing with children with acutely life-threatening disorders. Written by Imperial College healthcare NHS trust consultants, it is packed with guidelines and tips on how best to address a comprehensive range of clinical conditions. In paediatrics, the prognosis of acute diseases is very much dependent on the quality of clinical management during the initial hours after presentation. This pocket guide can be used immediately, at the bedside, to provide that all-important quick access to the correct information. The unique double-page organisation means the relevant information is accessible as soon as the book is opened. There is also space for the clinician to jot down personal comments and notes. Armed with this little book, clinicians will have all the correct information on hand, to use 'on the ground' in the emergency room.